Pengaruh Struktur Kepemilikan dan Struktur Dana Pihak Ketiga Terhadap Pengungkapan Tata Kelola pada Bank Syariah di Indonesia - Puspitasari, Farah Dwi; Sukmadilaga, Citra; Yuliafitri, Indri (AKTSAR: Jurnal Akuntansi Syariah, 2020)
This study aims to examine the influence of ownership structure and third party funds on corporate governance disclosure. The dependent variable used in this research is corporate governance disclosure measured by Islamic Corporate Governance (ICG). The independent variable in this research is ownership structure measured by blockholders ownership and third party funds measured by Restricted Profit Sharing Investment Account (RPSIA). The population in this study is the sharia banking industry registered in the Financial Services Authority (OJK) period 2012-2018. The sample in this research is 11 Sharia Bank. The data analysis method used in this study is the multiple linear regression. The results showed that the ownership structure and third party funds have a significant positive effect on corporate governance disclosure.